An overview of Hofstede-inspired country-level culture research in international business since 2006 - Beugelsdijk, Sjoerd; Kostova, Tatiana; Roth, Kendall (Journal of International Business Studies, 2017)
Kirkman, Lowe, & Gibson’s (2006) JIBS article summarized and critiqued international business research inspired by the most cited book in the field Hofstede’s 1980 Culture’s Consequences: International differences in work-related values (Hofstede [1980]2001). They identified a number of issues in this research and offered several recommendations for improving it in the future, thus laying a strong foundation for Hofstede-related work since 2006. In this commentary, we assess Kirkman et al.’s (2006) impact on the field. Our review shows that their ideas have informed and inspired their own and other scholars’ work and have led to significant progress in the way in which Hofstede’s framework has been used in international business in the last decade. Here, we specifically focus on the country-level culture studies and assess how research has implemented Kirkman et al.’s three main recommendations – to explore cultural dimensions beyond those introduced by Hofstede, to distinguish between country effects and cultural effects, and to show not only if culture matters but also how much it matters. In addition to the overview, we provide a comprehensive test of these recommendations showing how they can be put into research practice underscoring the theoretical and empirical relevance of the original 2006 article. Our commentary concludes with additional ideas on further strengthening Hofstede-inspired research at the country level of analysis.